Teacher Efforts In Improving Letter Knowledge Ability For Early Childhood Education - Reginal, Syindi Alshifa; Darmayanti, Nefi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The ability to recognize letters in students is the basis for students being able to read. This study uses the concept of learning while playing with word cards, picture cards, and letter cards as media. This study, recognizing letters, aims to discover and develop ways of learning to introduce letters to students with more fun methods and attract students' attention at PAUD Bunda Serdang Bedagai. This study uses a qualitative descriptive method. Data collection is done by interviews, observations, and field studies. In this study, the principal, teacher, and researcher worked together to use word cards, picture cards, and letter cards as media. This study uses a qualitative method with a case study approach. The research data is in the form of letter recognition activities using word cards, word cards, picture cards, and letter cards as media. Sources of data were obtained by researchers from school principals, class teachers, accompanying teachers, students, and several parents of students. Collecting data through observation, interviews, and documentation. Data analysis is done through data reduction, data presentation, drawing conclusions, and verification. The results showed that the teacher's efforts to improve the ability to recognize letters for early childhood students with the initial method were still less effective. Students could only know how to write, not know the letters well. But by using the word card method, picture cards, and letter cards, it is more effective for students to know letters better, not only in writing, but students know the shapes of letters and how to pronounce these letters randomly or sequentially.